Adult Children's Relationship to Parent Influences Their Views on Aging and Attitude Toward Own Aging. (October 2019) - Jung, Seojung; Jopp, Daniela S.
The goal of this study was to examine how the quality of relationship between parent and adult children influences adult children's views on aging and attitude toward their own aging and whether the effects of relationship qualities depend on parents' health and adult children's perceptions of how well their parents were aging. The sample included 217 adult children aged 18 to 73. Findings revealed that different parent–child relationship quality dimensions (i.e., support, conflict, depth, ambivalence) differentially influenced adult children's view on aging (positive and negative) and attitude toward own aging, and some of these effects depended on levels of parental health and the way adult children view how successfully their parents were aging. The quality of the relationship to one's parents has an important role in shaping adults' views on aging and experience of their own aging, highlighting the importance of incorporating the role of family context to further enhance our understanding of how individuals develop perceptions of aging.